A new species of Oozetetes De Santis (Hymenoptera: Chalcidoidea: Eupelmidae) from Colombia with an updated key for the bucheri species-group - Pérez-Benavides, A. Lucia; Serna, Francisco; Gibson, Gary A.p. (Zootaxa, 2016)
Oozetetes lucidus sp. nov. (Hymenoptera: Eupelmidae) is described from Colombia, South America, and through macrophotography compared with all described species in the bucheri species-group of Oozetetes De Santis. An illustrated key modified from Gibson (2004) is provided to distinguish females of the six described species of this group.